Moving Average Analysis of Islamic Stock Composite Index in Asia during Covid-19 Pandemic (Universitas Terbuka, 2023)
This study aims to determine the average growth of Islamic stock market conditions over the past three years since the Covid-19 pandemic hit through the proxy of the Islamic stock index through a comparative study in each country studied. This research method is descriptive quantitative, the nature of the data is data series, using secondary data sourced from daily reports downloaded from each country's stock exchange. The results of this research show that there is no significant difference between the first, second, and third years of the average movement of the sharia stock index in Asian countries that are the subject of the study (Indonesia, Malaysia, Thailand, China, Japan, India, and the United Arab Emirates). The countries that experienced a decrease in the Islamic index in the first yerat towards the second year (2020-2021) are Indonesia and China. And decrease index from the second year towards the third year (2021-2022) are Malaysia, Thailand, Japan, India, and the United Arab Emirates.